TECHNIQUES AND ACCURACY OF IDEATIONAL GRAMMATICAL METAPHOR TRANSLATION IN 'DIARY OF WIMPY KID' NOVELS - Nur Indah Arfianti; MR Nababan; Riyadi Santosa (Leksema: Jurnal Bahasa dan Sastra, 2018)
The ideational grammatical metaphor is a phenomenon emerging in lexico-grammar which causes new variant construction that is different from its original meaning and grammatical class. This article aims at classifying the translation techiques applied in Jeff Kinneyâ€™s Diary of Wimpy Kid novels and also the impact of its application in translating ideational grammatical metaphor which deals with accuracy aspect in translation quality assessment. This research was classified as descriptive-qualitative research with embedded case study research and it used systemic functional linguistics as its approach.. content analysis and focus group discussion were used for obtaining data. The data consisted of linguistic, that is the words representing ideational grammatical metaphors, and translation data, i.e: the analyses of translation techniques and translation accuracy. The techniques were analyzed by using Molina & Albir (2002) theoryÂ  whereas the accuracy was assessed based on TQA modified by Nababan, Nuraeni & Sumardiono (2012). Research findings showed that there were eight different translation techniques used for translating ideational grammatical metaphor in the novels. In addition, this average score of translation quality assessment showed that ideational grammatical metaphors in SL have been translated accurately to TL.